Vortical structures and behaviour of an elliptic jet impinging upon a convex cylinder - Long, J. (2020)
A study on a Reh = 2100, AR = 3 elliptic jet impinging upon different convex cylinders at a jet-to-cylinder separation distance of H/dh = 4 has been conducted. Laser induced fluorescence (LIF) and digital particle image velocimetry (DPIV) techniques were utilized to investigate the effects of cylinder-to-jet diameter-ratio (i.e. D/dh = 1.15, 2.3 and 4.6) and jet orientation upon the vortical structures and their behaviour. Results show that comparable flow developments occur along both convex surfaces and straight-edges when the elliptic jet minor-plane is aligned with the cylindrical axis (i.e. EJ1 configuration), while more non-uniform flow behaviour occurs when the elliptic jet major-plane is aligned with cylindrical axis (i.e. EJ2 configuration). Additionally, significant vortex engulfment behaviour between adjacent ring-vortices upon impingement is observed along the elliptic jet minor-plane regardless of exact impingement configuration, which subsequently leads to different flow modes. Braid vortices play a surprisingly interesting role, where they lead to cross-stream and upstream vortical motions for D/dh = 1.15 and 2.3 cylinders under EJ1 configuration. In contrast, they interact with adjacent jet ring-vortices and rib structures for D/dh = 4.6 cylinder. Proper orthogonal decomposition (POD) analyses provided additional information on the unique vortical behaviour identified in the flow fields, while momentum thickness profiles characterize the mixing layers in relation to the different configurations. Lastly, wall shear stress distributions under the above-mentioned flow conditions have also been determined and related to the vortical structures and behaviour.